Analiza porównawcza rachunkowości szkół wyższych w Polsce i USA - Koczuba-Sobieraj, Magdalena (Comparative Analysis of Accounting for Universities in the USA and Poland, 2005)
The paper focuses on accounting techniques for colleges and universities. A comparison of Polish and American approach to accounting for the universities shows some essential differences. The profit and loss account is not used in American university accounting. It is fair fund accounting which follows adequate standards. Polish accounting uses mainly Polish Accounting Act (1994) which does not specify any particular solutions in respect to university accounting.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 76-85